Identification of zona pellucida defects revealed a novel loss-of-function mutation in ZP2 in humans and rats - Zeng, Jun; Sun, Ying; Zhang, Jing; Wu, Xiaozhu; Wang, Yan; Quan, Ruping; Song, Wanjuan; Guo, Dan; Wang, Shengran; Chen, Jianlin; Xiao, Hongmei; Huang, Hua-Lin (Frontiers in Endocrinology, 2023)
Introduction Human zona pellucida (ZP) plays an important role in reproductive process. Several rare mutations in the encoding genes (ZP1, ZP2, and ZP3) have been demonstrated to cause women infertility. Mutations in ZP2 have been reported to cause ZP defects or empty follicle syndrome. We aimed to identify pathogenic variants in an infertile woman with a thin zona pellucida (ZP) phenotype and investigated the effect of ZP defects on oocyte gene transcription. Methods We performed whole-exome sequencing and Sanger sequencing of genes were performed for infertilite patients characterized by fertilization failure in routine in vitro fertilization (IVF). Immunofluorescence (IF) and intracytoplasmic sperm injection (ICSI) were used in the mutant oocytes. Single-cell RNA sequencing was used to investigate transcriptomes of the gene-edited (Zp2mut/mut) rat model. Biological function enrichment analysis, quantitative real-time PCR (qRT-PCR), and IF were performed. Results We identified a novel homozygous nonsense mutation of ZP2 (c.1924C > T, p.Arg642X) in a patient with non-consanguineous married parents. All oocytes showed a thin or no ZP under a light microscope and were fertilized after ICSI. The patient successfully conceived by receiving the only two embryos that developed to the blastocyst stage. The immunofluorescence staining showed an apparently abnormal form of the stopped oocytes. We further demonstrated a total of 374 differentially expressed genes (DEGs) in the transcriptome profiles of Zp2mut/mut rats oocytes and highlighted the signal communication between oocytes and granulosa cells. The pathway enrichment results of DEGs showed that they were enriched in multiple signaling pathways, especially the transforming growth factor-β (TGF-β) signaling pathway in oocyte development. qRT-PCR, IF, and phosphorylation analysis showed significantly downregulated expressions of Acvr2b, Smad2, p38MAPK, and Bcl2 and increased cleaved-caspase 3 protein expression. Discussion Our findings expanded the known mutational spectrum of ZP2 associated with thin ZP and natural fertilization failure. Disruption of the integrity of the ZP impaired the TGF-β signaling pathway between oocytes and surrounding granulosa cells, leading to increased apoptosis and decreased developmental potential of oocytes.